A Novel Pedicle Screw with Mobile Connection: A Pilot Study. (3rd March 2014) - Tokuhashi, Yasuaki; Oshima, Masashi; Ajiro, Yasumitsu; Uei, Hiroshi
Abstract : To prevent adjacent disc problems after spinal fusion, a pedicle screw with a mobile junction between the head and threaded shaft was newly developed. The threaded shaft of the screw has 10 degrees mobility in all directions, but its structure is to prevent abnormal translation and tilting. This screw was evaluated as follows: (1) endurance test: 10 6 times rotational stress was applied; (2) biological reactions: novel screws with a mobile head and conventional screws with a fixed head were inserted into the bilateral pedicles of the L3, L4, and L5 in two mini pigs with combination. Eight months after surgery, vertebral units with the screw rod constructs were collected. After CT scan, the soft and bony tissues around the screws were examined grossly and histologically. As a result, none of the screws broke during the endurance test stressing. The mean amount of abrasion wear was 0.0338 g. In the resected mini pig section, though zygapophyseal joints between fixed-head screws showed bony union, the amount of callus in the zygapophyseal joints connected with mobile-head screws was small, and joint space was confirmed by CT. No metalloses were noted around any of the screws. Novel screws were suggested to be highly durable and histologically safe.